Análisis técnico-financiero de las diferentes alternativas para la medición in-line de la viscosidad del polímero durante su proceso de inyección (2019)
In this project, different commercial in-line viscometers were analyzed from a technical point of view for the real-time measurement of the viscosity of polymer solutions in polymer injection processes in Colombia, comparing the physical principles, operating ranges, advantages , disadvantages; In addition to this, an economic analysis of the viscometers provided in the market survey was carried out, comparing them with the current measurement methodology of Ecopetrol S.A. Based on the above, it was determined which one or which fit each case of study. In the first instance, the description and analysis of eight commercial in-line viscometers from different multinational companies were made, which have greater applicability in the hydrocarbon and polymer industry; in order to develop a technical comparison of its physical principles, operational ranges and limitations. Subsequently, the operating conditions that govern the five polymer injection pilots executed by Ecopetrol SA were described, and variables that directly affect the integrity of the measurement of the polymer solution to surface conditions were identified and analyzed, identifying the viscometers suitable for monitoring the viscosity of the polymer solution in each pilot. Finally, a financial analysis of the technically feasible and commercially available viscometers was conducted through a market survey, which were compared with the current methodology used in Ecopetrol SA for the measurement of the viscosity of the polymer solution, this analysis was performed by flow of cash to obtain the net present value (NPV), internal rate of return (IRR), and investment efficiency (EFI) using fixed CAPEX of the pilot and using the OPEX of each one of the measurement alternatives.